Dilemmas for Sustainable Development in Poland - Jaśkiewicz, Jacek (Problemy Ekorozwoju, 2008)
The article consists of three parts. The first presents the aspirations of Polish society as these concern global objectives of environment protection, while the next describes accession commitments and new challenges relating to environment protection. The final part is devoted to the popularization of the philosophy of sustainable development in all its dimensions. The article describes the situation following revision of the Lisbon Strategy (objectives to 2010) as well as the EU’s Sustainable Development Strategy, but also prior to the parliamentary debate on the National Environmental Policy for the years 2007-2010 with account taken of prospects for the years 2011-2014, as well as prior to the verification of the Polish Sustainable Development Strategy.